Polymicrobial infective endocarditis caused by Neisseria sicca and Haemophilus parainfluenzae. (2016) - Koshkelashvili, Nikoloz; Shah, Mahek; Codolosa, J. Nicolas; Climaco, Antonette
Abstract: Infective endocarditis is a common clinical problem in industrialized countries. Risk factors include abnormal cardiac valves, a history of endocarditis, intracardiac devices, prosthetic valves and intravenous drug use. We report a case of polymicrobial infective endocarditis in a 33 year-old female with a history chronic heroin use caused by Neisseria sicca and Haemophilus parainfluenzae . We believe the patient was exposed to these microbes by cleansing her skin with saliva prior to injection. Pairing a detailed history with the consideration of atypical agents is crucial in the proper diagnosis and management of endocarditis in patients with high-risk injection behaviors.